P01.073 Hypofractionated radiation therapy (over 3 weeks) can replace conventional radiation therapy schedule (over 6 weeks) in newly diagnosed glioblastoma patients? The times are ripe. (19th September 2018) - Navarria, P; Clerici, E; Pessina, F; Franzese, C; Bello, L; Simonelli, M; Tomatis, S; Leonetti, A; Scorsetti, M
Abstract: Background: The standard of care for newly diagnosed glioblastoma multiforme consists of surgery, followed by conventional radiation therapy (CRT) with concurrent and adjuvant temozolomide chemotherapy. All the attempts to enhance the efficacy of RT were unsuccessful. Recently, the impact of hypofractionated radiation therapy (HFRT) has been investigated with promising results. We conducted a prospective phase II study, and subsequently a propensity score analysis to evaluate whether HFRT can be comparable to CRT. Material and Methods: In the phase II study, all patients underwent surgery, HFRT with concomitant and adjuvant temozolomide chemotherapy. The dose prescribed was 60 Gy over 3 weeks. The propensity score matched analysis compared CRT 60 Gy/30 fractions vs HFRT 60 Gy/15 fractions in an homogeneous population for patients, tumor and treatments characteristics. The two cohorts were selected by using a logistic regression considering age, KPS, extent of surgery, MGMT and IDH status, recorded as factors affecting survival. Results: From August 2013 to December 2015, 97 newly diagnosed GBM patients were treated in the phase II study. The median, 1, 2-year OS were 16 months, 72.2%, and 30.4%. All patients completed the schedule HFRT plan. Neuropsychological scores before and after HFRT remained unchanged. The analysis showed no detrimental effect of HFRT on cognitive functions (language, short and long term verbal and visuo-spatial memory, working memory, attentive and executive functions). Particularly, a significant performance improvement was detected. The greater benefit of treatment was observed in patients younger than 60 years and with KPS 100 with 40% and 50% alive beyond two years, respectively (p=<<0.01). For propensity score matched analysis a total of 267 patients were included; before PSM 169 were in CRT-group and 98 in HRFT-group. After 1:1 matching, 82 patients resulted in each group. The median OS time was 17.9 months for the CRT group and 16.7 months for the HFRT-group; the 1, 2, 3-year OS rates were 75.6%, 32.7%, and 15.5% for the CRT-group, and 75.6%, 33.3%, and 18.9% for the HFRT-group No statistically significant differences were recorded between the two radiation therapy treatments performed (p value = 0.8). Conclusion: in our evaluation HFRT schedule has proven to be not inferior to CRT in terms of outcome, and less burdensome for these poor prognosis patients. Open questions remain the optimal radiation total doses to deliver and the schedule to utilize, but HFRT within a multimodal therapeutic approach, seems a way forward to improve the outcome of patients with glioblastoma.